Effects of various environments on epigenetic settings and chromosomal damage. (15th April 2023) - Rossnerova, Andrea; Elzeinova, Fatima; Chvojkova, Irena; Honkova, Katerina; Sima, Michal; Milcova, Alena; Pastorkova, Anna; Schmuczerova, Jana; Rossner, Pavel; Topinka, Jan; Sram, Radim J.
Abstract: Air pollution is a dominant environmental exposure factor with significant health consequences. Unexpectedly, research in a heavily polluted region of the Czech Republic, with traditional heavy industry, revealed repeatedly the lowest frequency of micronuclei in the season with the highest concentrations of air pollutants including carcinogenic benzo[a]pyrene (B[a]P). Molecular findings have been collected for more than 10 years from various locations of the Czech Republic, with differing quality of ambient air. Preliminary conclusions have suggested adaptation of the population from the polluted locality (Ostrava, Moravian-Silesian Region (MSR)) to chronic air pollution exposure. In this study we utilize the previous findings and, for the first time, investigate micronuclei (MN) frequency by type: (i) centromere positive (CEN+) MN, representing chromosomal losses, and (ii) centromere negative (CEN-) MN representing chromosomal breaks. As previous results indicated differences between populations in the expression of XRCC5, a gene involved in the non-homologous end-joining (NHEJ) repair pathway, possible variations in epigenetic settings in this gene were also investigated. This new research was conducted in two seasons in the groups from two localities with different air quality levels (Ostrava (OS) and Prague (PG)). The obtained new results show significantly lower frequencies of chromosomal breaks in the OS subjects, related to the highest air pollution levels ( p < 0.001). In contrast, chromosomal losses were comparable between both groups. In addition, significantly lower DNA methylation was found in 14.3% of the analyzed CpG loci of XRCC5 in the population from OS. In conclusion, the epigenetic adaptation (hypomethylation) in XRCC5 involved in the NHEJ repair pathway in the population from the polluted region, was suggested as a reason for the reduced level of chromosomal breaks. Further research is needed to explore the additional mechanisms, including genetic adaptation. Graphical abstract: Image 1 Highlights: The association of chronic air pollution exposure with chr. damage was evaluated. The unexpectedly reduced MN frequency linked with high air pollution was explored. A decreased frequency of chromosomal breaks was observed. Simultaneous hypomethylation in XRCC5 was detected. Epigenetic modification of XRCC5 could contribute to reduced chromosomal damage.